MEMAHAMI DAN MELIHAT DINAMIKA CURANMOR DIWILAYAH POLSEK TAMPAN KOTA PEKANBARU - Rinaldi, Kasmanto (EDUTECH CONSULTANT, 2017)
Crime is an issue that will always be in people's lives. All efforts in the face of evil will not be able to destroy it, the crime can only be reduced and prevented, especially crime of theft of motor vehicles. Prevention of crime as a business that includes the actions that have special purposes to minimize the scope and violence of a violation either through reduction of opportunities to commit crime through the provision of business or influence to people who could potentially become offenders as well as to the general public. By using a qualitative approach in reflecting the existing phenomenological perspective, official institutions responsible for crime prevention efforts is the police. However, because of limited facilities and infrastructure owned by the police has resulted in no effectivity the task.Furthermore, the police are also not likely to reach the ideal stage of fulfillment facilities and infrastructure related to crime prevention efforts. Therefore, it is highly desirable community participation in crime prevention activities into something that is expected by the police.